2008
DOI: 10.1111/j.1931-0846.2008.tb00295.x
|View full text |Cite
|
Sign up to set email alerts
|

ResurgenT Mexican Phoenix*

Abstract: ABSTRACT. Popular impressions of Phoenix, Arizona perpetuate the notion that this metropolitan area is an overwhelmingly Anglo place. We challenge this assertion and demonstrate that the city has substantial Mexican roots and is presently being shaped by a vibrant, resurgent Mexican population. Employing historical records, surveys, and landscape data, we articulate the Mexican character of early Phoenix and highlight how the revival of Mexican Phoenix has transformed the urban landscape. We then relate how P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…It is especially indebted to the indigenous Hohokam people and their extensive canal building, Jack Swilling, a Confederate veteran who set up the Swilling Irrigation and Canal Company, and Swilling's wife, Trinidad Meija Escalante of Hermosillo, known as the ''Mother of Phoenix'' (Skop and Menjivar 2001;Lukinbeal et al 2010). The largest Hispanic population increase to the area, however, occurred only in the last 30 years , as Phoenix has become a destination and transitional node for both legal and illegal Hispanic immigrants (Singer and Suro 2002;Oberle and Arreola 2008). In 2010 the state passed one of the most severe antiillegal immigration bills of its time in the United States, Arizona Senate Bill 1070 (SB1070), or the ''Support Our Law Enforcement and Safe Neighborhoods Act.''…”
Section: Geographic and Political Contextmentioning
confidence: 98%
See 1 more Smart Citation
“…It is especially indebted to the indigenous Hohokam people and their extensive canal building, Jack Swilling, a Confederate veteran who set up the Swilling Irrigation and Canal Company, and Swilling's wife, Trinidad Meija Escalante of Hermosillo, known as the ''Mother of Phoenix'' (Skop and Menjivar 2001;Lukinbeal et al 2010). The largest Hispanic population increase to the area, however, occurred only in the last 30 years , as Phoenix has become a destination and transitional node for both legal and illegal Hispanic immigrants (Singer and Suro 2002;Oberle and Arreola 2008). In 2010 the state passed one of the most severe antiillegal immigration bills of its time in the United States, Arizona Senate Bill 1070 (SB1070), or the ''Support Our Law Enforcement and Safe Neighborhoods Act.''…”
Section: Geographic and Political Contextmentioning
confidence: 98%
“…As they say in Tucson: ''We didn't cross the border, the border crossed us'' (Burke 2002, 6). Since its inception, Phoenix has been reliant on Latinos for development (Oberle and Arreola 2008). It is especially indebted to the indigenous Hohokam people and their extensive canal building, Jack Swilling, a Confederate veteran who set up the Swilling Irrigation and Canal Company, and Swilling's wife, Trinidad Meija Escalante of Hermosillo, known as the ''Mother of Phoenix'' (Skop and Menjivar 2001;Lukinbeal et al 2010).…”
Section: Geographic and Political Contextmentioning
confidence: 99%
“…Hispanics are the second most segregated group following African Americans and experienced increasing amounts of segregation over the period from 1980 to 2000 (Iceland, Weinberg, and Steinmetz 2002). Hispanics have also suffered from a systematic undercounting; for instance, with regard to their presence among the homeless (Conroy and Heer 2003), in the urban historical record (Oberle and Arreola 2008;Lukinbeal, Arreola, and Lucio 2010), and among the ranks of suburbanites (Odem 2008). In addition, refining the understanding of Hispanic participation and experiences in U.S. cities has acquired particular urgency of late, for there is evidence that today's Hispanic population is losing ground on a variety of fronts vis-àvis non-Hispanic whites (Haney-López 2006;García 2007).…”
Section: Hispanic Segregation and "The Divide"mentioning
confidence: 99%
“…accepted by social scientists as a social construct; work by geographers has shown that a key factor in understanding the social construction of whiteness by Latinos is place (Price, 2009;Oberle and Arreola, 2008;Winders et al, 2005;Winders, 2005;Radcliffe, 1999). As Price (2009) To what extent scale plays here, i.e., race in the neighborhood, cannot be easily teased out using the quantitative above.…”
mentioning
confidence: 99%
“…For immigrants to the United States, the ethnic and racial structure is particularly relevant, as ideas and understandings of race are place-and context-dependent. This is because the social construction of race in general, and whiteness in particular, is highly place-specific and "has constituted a relatively porous social formation, if variously so over time and place (Price, 2009: 18;Oberle and Arreola, 2008;Martínez, 2000;Almaguer, 1998). Latin…”
mentioning
confidence: 99%